PENGARUH TOTAL ASET, SOLVABILITAS, OPINI AUDIT DAN PROFITABILITAS TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan LQ45 yang Terdaftar di BEI Periode Tahun 2014-2015)”. - Arif Anshari Raswen; Azwir Nasir; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze total assets, solvency, audit opinion and profitability of audit delay at LQ45 company located in Indonesia Stock Exchange in the year 2010-2015.Sampling method used is purposive sampling and sample result of 36 companies.The data used is secondary data, namely the financial statements of companies listed on the Indonesia Stock Exchange in 2004-2015. In order to prove the hypothesis, multiple regression testing is performed. Testing simultaneously. Partial test results seen there are 1 of 4 factors that affect the audit delay, is profitability. Total assets, solvency and audit opinion are not have an effect against audit delay.Keywords : Total Asets, Solvency, Auditor’s Opinion, Profitability, Audit Delay